2016
DOI: 10.3389/fpsyg.2016.00413
|View full text |Cite
|
Sign up to set email alerts
|

Brief Online Training Enhances Competitive Performance: Findings of the BBC Lab UK Psychological Skills Intervention Study

Abstract: In conjunction with BBC Lab UK, the present study developed 12 brief psychological skill interventions for online delivery. A protocol was designed that captured data via self-report measures, used video recordings to deliver interventions, involved a competitive concentration task against an individually matched computer opponent, and provided feedback on the effects of the interventions. Three psychological skills were used; imagery, self-talk, and if-then planning, with each skill directed to one of four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…The absence of performance feedback during the task meant that participants could not develop schema on how they could use feedback from performance to gauge how much effort to use. Self-talk can raise emotional arousal which can lead to improved performance via increased effort [ 4 ]. Further, research has indicated that it is possible to learn self-talk to raise arousal using brief interventions [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of performance feedback during the task meant that participants could not develop schema on how they could use feedback from performance to gauge how much effort to use. Self-talk can raise emotional arousal which can lead to improved performance via increased effort [ 4 ]. Further, research has indicated that it is possible to learn self-talk to raise arousal using brief interventions [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological qualities such as improved confidence can be developed via skills training [ 3 ]. Skills found to be effective in improving endurance performance include cognitively based approaches such as the use of imagery, self-talk, and goal setting [ 4 , 5 , 6 ]. In the present study, we focus specifically on self-talk, which can be defined as an act of syntactically recognizable communication [ 7 ], articulated either out loud or as a voice inside the head [ 8 ], addressed to the self, with interpretative elements associated to its content [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the usual amount of exercise and adjusting diet in long-term appear to be the most appropriate procedures when performed throughout the competitive season (26). b) When considering the psychological aspects related to weight reduction, athletes consider acute weight loss as a mentally important part of the pre-competitive preparation (23,24). c) The individuals who are the most influential in teaching athletes strategies for weight loss are typically the coach, training partners or former athletes, educational programs should focus on providing them with full explanations of how to properly advise MMA fighters about weight management procedures (14).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Consequently, whether relaxation cues can be effective as part of the brief contact interventions accessible to the majority of athletes (e.g., online, at pre-race events; Lane et al, 2016;Meijen, Day, & Hays, 2016) remains to be seen. Furthermore, which cues are most effective to induce relaxation is unknown.…”
Section: Mmentioning
confidence: 99%